Pisang Epe Sebagai Representasi Identitas Kuliner Lokal: Kajian Gastronomi terhadap Daya Tarik Wisata Kota Makassar - Utami, Meidy Putri; Prambudi, Yogi; Nasrullah; Hardianti (Jurnal Pariwisata Indonesia, 2025)
This study examines Pisang Epe, a traditional grilled banana snack from Makassar, as a representation of local culinary identity and as a key attraction within the city’s emerging gastronomic tourism. Using a qualitative case study design, data were collected through participant observation at Pantai Losari, in-depth interviews with vendors and tourists, and analysis of promotional materials and social media content. The analysis explores how historical–geographical, gastronomic, and socio-cultural dimensions are articulated through this food. Findings show that Pisang Epe embodies coastal agrarian heritage while being strongly anchored to Pantai Losari, creating a distinctive sense of place for residents and visitors. Its simple but specific preparation techniques and sensory characteristics construct an authentic culinary identity that differentiates it from other banana-based products, even as contemporary toppings are introduced to meet changing tourist preferences. The study also reveals that consumption of Pisang Epe functions as a social ritual that mediates interaction between locals and tourists, enhances memorable tourism experiences, and supports the livelihoods of micro and small enterprises. Overall, Pisang Epe contributes to strengthening Makassar’s city branding as a gastronomic destination and demonstrates how everyday street food can be strategically leveraged in culturally grounded and sustainable culinary tourism development.